Nursing experience of a case with immune pneumonia after repeated use of toripalimab (1例多次使用特瑞普利单抗并发免疫性肺炎的护理体会) - CHEN Juan (陈娟); ZHANG Rong (张容); LAI Jianhong (赖建红) (中西医结合护理)
This paper summarized the nursing process of a case of immune pneumonia after repeated use of Treprilimab. The nursing measures included respiratory system nursing, medication nursing, psychological nursing, discharge rehabilitation guidance and follow-up. (本文总结1例多次使用特瑞普利单抗并发免疫性肺炎的护理措施, 包括呼吸系统护理、用药护理、心理护理、出院康复指导及随访等。)